(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Educational institutions authority did not show interest in advanced technology, some organizations feel that it is not necessary. Users growing demands and good suggestions develop library and library activity. If library users (teachers/ students) aware and demand for digital facilities like e-resources and networking services and databases then library development start. Many institutions and library staff feel fear and stress about new technology; it is evident that, these many problems reduce the importance of digital library. Researcher in this research project finds out the actual situation of college libraries and education institutions attitude towards digital technology. Researcher also tries to know teachers interest, teachers opinion about audio video aids, digital technologies equipment in teachings process.